2023
DOI: 10.3390/ijms24021569
|View full text |Cite
|
Sign up to set email alerts
|

Different Photosynthetic Response to High Light in Four Triticeae Crops

Abstract: Photosynthetic capacity is usually affected by light intensity in the field. In this study, photosynthetic characteristics of four different Triticeae crops (wheat, triticale, barley, and highland barley) were investigated based on chlorophyll fluorescence and the level of photosynthetic proteins under high light. Compared with wheat, three cereals (triticale, barley, and highland barley) presented higher photochemical efficiency and heat dissipation under normal light and high light for 3 h, especially highla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…The levels of photosynthetic pigments (chlorophylls and carotenoids) are closely related to the photosynthetic capacity of higher plants under environmental stress. It has been shown that a high content of chlorophylls can allow the absorption of more light energy, and therefore result in a higher photosynthetic capacity [57]. In addition, the chlorophyll A/B ratio has also been used as an indicator of plant stress [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of photosynthetic pigments (chlorophylls and carotenoids) are closely related to the photosynthetic capacity of higher plants under environmental stress. It has been shown that a high content of chlorophylls can allow the absorption of more light energy, and therefore result in a higher photosynthetic capacity [57]. In addition, the chlorophyll A/B ratio has also been used as an indicator of plant stress [58,59].…”
Section: Discussionmentioning
confidence: 99%